Format independence of audio and video in multimedia database systems. (26th September 2008) - Suchomski, Maciej; Meyer-Wegener, Klaus
Format independence is a crucial aspect of data independence in databases, but it is rarely offered for continuous media data (such as audio and video) in multimedia databases. It can be provided by a real-time transformation supported by prepared meta-data, which is most suitable for systems with a low frequency of use for certain continuous multimedia data and a high probability of differentiation between clients accessing these data. This paper focuses on such a real-time transformation that is based on the RETAVIC framework. Additionally, the application scenario and requirements for long-term internal storage formats are discussed.